KONTRADIKSI PENGATURAN KERJA KONTRAK DAN OUTSOURCING DALAM UNDANG-UNDANG KETENAGAKERJAAN DENGAN UNDANGUNDANG DASAR 1945 - Ni Ketut Bagiastuti (Politeknik Negeri Bali, 2014)
Labor is basically the backbone of national development, because without workers the development can not run smoothly. This is why the government pays great attention on labor by issuing Law No. . 13 Year 2013 on Employment . In Act No. . 13 In 2013 it is set the protection of labor. One is the arrangement of outsourcing and contract labor. But it turns out in field the arrangement of outsourcing and contract labor undergo many irregularities . The arrangement of outsourcing and contract labor was contrary to several articles in the 1945 Constitution as the basic law of the highest in Indonesia . The purpose of this study is to conduct an inventory and analysis of the implementation of the Employment Act especially with regard to outsourcing and contract labor force as opposed to the sound of some articles of the 1945 Constitution . The goal is for the perfection of the Employment Act ,namely Law No. 13 of 2003.